Epigenetic and Transcriptional Pre-patterning—An Emerging Theme in Cortical Neurogenesis - Albert, Mareike; Huttner, Wieland B. (Frontiers in Neuroscience, 2018)
Neurogenesis is the process through which neural stem and progenitor cells generate neurons. During the development of the mouse neocortex, stem and progenitor cells sequentially give rise to neurons destined to different cortical layers and then switch to gliogenesis resulting in the generation of astrocytes and oligodendrocytes. Precise spatial and temporal regulation of neural progenitor differentiation is key for the proper formation of the complex structure of the neocortex. Dynamic changes in gene expression underlie the coordinated differentiation program, which enables the cells to generate the RNAs and proteins required at different stages of neurogenesis and across different cell types. Here, we review the contribution of epigenetic mechanisms, with a focus on Polycomb proteins, to the regulation of gene expression programs during mouse neocortical development. Moreover, we discuss the recent emerging concept of epigenetic and transcriptional pre-patterning in neocortical progenitor cells as well as post-transcriptional mechanisms for the fine-tuning of mRNA abundance.